Surgical Treatment of Obstetric Plexus Lesions by Direct Coaptation Compared to Sural Nerve Graft Interposition - Mai, Justus; Raak, Christa Kunigunde; Ostermann, Thomas; Bahm, Jörg; Scharbrodt, Wolfram (Journal of Brachial Plexus and Peripheral Nerve Injury, 2025)
Background To date, there are no uniform guidelines for the treatment of obstetric plexus lesions in German-speaking countries. An end-to-end direct suture after resection of trunk neuroma is recommended for surgical treatment if tension-free coaptation is possible, whereas the use of autologous nerve grafts bridging the gap between the adaptation margins is advised by consensus if tension-free coaptation is impossible.Objective The aim of the study was to investigate which reconstruction strategy may provide a better recovery of motor function for patients after obstetric brachial plexus lesion.Methods This study compared postoperative functional outcome after obstetric brachial plexus palsy from a patient collective including a total of 43 children. The surgical techniques of plexus reconstruction by end-to-end coaptation versus the use of sural nerve interposition graft have been analyzed. Therefore, the degrees of active motion of abduction and external rotation in the shoulder joint, and flexion in the elbow joint were assessed using the neutral zero method.Results For abduction in the shoulder joint, significantly better motor function was found in the group with direct sutures (p = 0.033). For external rotation in the shoulder joint and flexion in the elbow joint, there was no statistically significant difference between the groups (p = 0.284 and p = 0.270, respectively).Conclusions This study could not demonstrate absolute superiority of either reconstruction method. Slight evidence was found for a better functional outcome for plexus reconstruction by direct coaptation. Further arguments support a better suitability of plexus reconstruction by direct suture if its use is justifiable.
Keywords: obstetric brachial plexus palsy; direct coaptation; sural nerve graft; microsurgery